To be or not to be . . . a flower? A test of possible cues influencing hunting site selection in subadult females of the crab spider Epicadus heterogaster (Guerin 1812) (Araneae: Thomisidae) - Peixoto, Paulo Enrique C.; Souza, Jose C. [UNESP]; Schramm, Jose Eneas (Taylor & Francis Ltd, 2012)
Females of some Thomisidae species are known to use visual and olfactory stimuli to select high quality hunting sites. However, because studies about foraging behavior in this family are concentrated on a few species, the comprehension of the process related to hunting behavior evolution in crab spiders may be biased. In this study we investigated the hunting site selection of a previously unstudied crab spider, Epicadus heterogaster. We performed three experiments to evaluate the hypothesis that subadult females are able to use visual and olfactory stimuli to select hunting sites. In the first experiment, females did not preferentially select flower paper models that matched their body coloration. However, after choosing a model that had the same body color as the spider, they remained on it for longer periods than on models with different colors. In the second experiment, females did not discriminate between flower paper models, natural flower models and crumpled paper models. Females did also not discriminate among different olfactory stimuli in the third experiment. It is possible that subadult females of E. heterogaster need to establish and experience a given hunting site before evaluating its quality. However, it remains to be investigated if they use UV cues to select a foraging area before experiencing it.
Keywords: Habitat selection; visual signals; chemical signals; optimal foraging theory; crab spiders; Brazil